(untitled) (ShodhVarta, 2023)
This research article presents an in-depth analytical study of ‘Ballad of the Warrior Girl Kuyili’ written by Vanvil K. Ravi. The ballad is an important literary work that explores the themes of courage, heroism, sacrifice, resistance, and the role of women and the representation of marginalized voices in historical narratives. The research article reveals how the character of ‘Kuyili’ emerges as a symbol of wisdom and bravery while challenging traditional caste and gender norms. Along with this, a detailed analysis of the ballad’s text, its historical context, literary devices, and cultural significance has been done in this research article, which throws light on the purpose of the article and the multifaceted dimensions of this poignant literary work. ‘Kuyili’ is not only a literary work but also a cultural artifact that speaks to the hearts of the people of present-day Tamil Nadu, Which holds a special place in the folk literature there. This research article examines the cultural and historical significance of this ballad and its influence on contemporary discussions regarding the role of women in history.